Natural Disaster Mitigation on Elementary School Teachers: Knowledge, Attitude, and Practices - Atmojo, Setyo Eko (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the level of knowledge, attitudes, and practice of teachers in disaster education in elementary schools. This study uses questionnaires distributed to teachers in disaster-prone schools. The data taken are age, gender, subjects taught, recent education, experience in disaster education training, knowledge level, attitude, and practice of disaster education. Respondents who have a good knowledge level are 51.5%, enough knowledge level is 39.4%, and less knowledge level is 9.1%. As many as 98.9% of respondents have a positive attitude and 1.1% have a negative attitude. There are 90.9% of respondents have ever taught and 9.1% have never taught disaster education. This study concludes that teachers of Elementary in disaster-prone schools generally have good knowledge of disaster education, agree that disaster education becomes part of the curriculum, and have taught disaster education to students.